HUBUNGAN KELEBIHAN JAM KERJA DENGAN KEJADIAN HIPERTENSI PADA PEKERJA PT. ASTORIA BANGUN PERKASA BATAM - Saiful Batubara; Lady Tria Rannie; Rusdani Rusdani (Fakultas Kesehatan Masyarakat Institut Kesehatan Deli Husada Delitua, 2019)
Background: This study aims to determine the relationship of excess working hours with the incidence of hypertension in PT. Astoria Build Mighty Batam. Methods: This research method uses quantitative types with observational analytic research designs and Cross Sectional approaches. The population of this research is all PT. Astoria Bangun Perkasa which amounts to 60 workers. The instruments used in data retrieval are the Sphygmomanometer, the stethoscope and company data. Results: The results of the univariate analysis showed that most workers experienced overtime hours of 17 people (34%) while workers who did not experience excess hours worked as many as 33 people (66%). Workers who experienced hypertension were 7 people (14%) while workers who did not have hypertension were 43 people (86%). The results of the bivariate analysis with the chi-square test showed that there was a significant relationship between excess work hours and hypertension.